A child with autism, behavioral issues, and dysmorphic features found to have a tandem duplication within CTNND2 by mate‐pair sequencing. Issue 3 (8th December 2019) - Miller, Danny E.; Squire, Audrey; Bennett, James T.
Abstract: We describe a 5‐year‐old male with developmental delay, behavioral problems, and dysmorphic features who was found by microarray to have a 93‐kb duplication of uncertain significance that fully encompasses the third exon of CTNND2 (delta catenin). Mate‐pair sequencing was used to determine that the duplication is tandem and is predicted to lead to CTNND2 haploinsufficiency. Haploinsufficiency for CTNND2 has been shown to result in developmental delay and intellectual disability, providing a unifying diagnosis for this patient. His features overlap those associated with the larger cri‐du‐chat deletion of this region, expanding the clinical phenotype of isolated CTNND2 variants. The use of mate‐pair sequencing to determine the orientation of the small duplication was essential to the diagnosis and avoided the use of exome sequencing, which would not have defined the arrangement of the duplication. This is only the second reported patient, to our knowledge, with a single exon duplication of CTNND2 .